Penicillin induced toxic epidermal necrolysis with secondary impetiginization: a rare case - Ramineni, Hari Babu; Muttineni, Chandini; Munnangi, Srividya; Suryadevara, Vidyadhara (International Journal of Research in Medical Sciences, 2017)
Drug induced allergic reactions can be categorized into IgE-mediated and non-IgE mediated hypersensitivity reactions. Symptoms of IgE-mediated reactions are angioedema, bronchospasm, anaphylaxis, and urticaria that appears within 72 hours and those which are Non-IgE mediated hypersensitivity reactions include morbilliform eruptions, interstitial nephritis, hemolytic anemia, serum sickness, thrombocytopenia, and erythema multiforme, after 72 hours. TEN is defined as an extensive detachment of full-thickness epidermis most often related to an adverse drug reaction. We report a rare case of penicillin induced toxic epidermal necrolysis with Secondary Impetigination in a 38-year-old male patient with complaints of rashes all over the body, chest pain and dry tongue since seven days. Based on history and clinical examination patient was diagnosed as of penicillin induced toxic epidermal necrolysis with secondary impetigination and was successfully treated with antihistamines, parenteral antibiotics and corticosteroids.